KOMUNIKASI PERSUASIF TERHADAP PENYANDANG DISABILITAS, ANAK, DAN LANSIA (Studi pada Bidang Inovasi Pelayanan Dinas Kependudukan dan Pencatatan Sipil Kabupaten Muara Enim) - Ananda Putra ilham Wicaksana (Jurnal Prodi Ilmu Komunikasi, 2023)
This research is entitled “Persuasive Communication for Persons with Disabilities, Children and the Elderly” (Study in the Field of Service Innovation for the Population and Civil Registration Office of Muara Enim Regency). The purpose of this research is to find out how persuasive communication is in the field of service innovation in line with the Record Program to Visit Children with Disabilities in Children and the Elderly. The research method used is the qualitative method. The data collection techniques are interviews, journals, books, and documentation. The theory used is the AIDDA theory. This theory explains that a persuasive activity (persuasion) begins with attention and ends with action. The result of this research is persuasive communication carried out in the field of service innovation in the rendang pedas program using 5 stages of aidda theory, namely: attention by introducing this program through social media, then interest is carried out by informing that this program is carried out by pick-up. Then grow the desire to make access easier only by reporting to the local government or reporting independently via whatsapp, In making decisions to provide assistance and provide an understanding of the importance of electronic ID cards, Finally, the act of recording ID cards biometrics carried out by persons with disabilities Keywords : Disability, Elderly, Persuasive, Service